2022
DOI: 10.3390/ma15227886
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Phosphorus-Doped Silicon Annealed by Continuous-Wave Laser Beam at High Scan Speed

Abstract: We report an in-depth analysis of phosphorus (P)-doped silicon (Si) with a continuous-wave laser source using a high scan speed to increase the performance of semiconductor devices. We systematically characterized the P-doped Si annealed at different laser powers using four-point probe resistance measurement, transmission electron microscopy (TEM), secondary-ion mass spectroscopy, X-ray diffractometry (XRD), and atomic force microscopy (AFM). Notably, a significant reduction in sheet resistance was observed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The phosphorus concentration pro le of the reference emitter 60 Ω/sqr present a shallow depth of 0.4µm and is presented by black line. Similar to others [21] it was found that the junction depth increases when increasing the laser power. The highest phosphorus concentrations were detected near the surface for reference emitter without laser ablation.…”
Section: Optimization Of Laser Dopingsupporting
confidence: 88%
“…The phosphorus concentration pro le of the reference emitter 60 Ω/sqr present a shallow depth of 0.4µm and is presented by black line. Similar to others [21] it was found that the junction depth increases when increasing the laser power. The highest phosphorus concentrations were detected near the surface for reference emitter without laser ablation.…”
Section: Optimization Of Laser Dopingsupporting
confidence: 88%